2009
DOI: 10.1348/135532508x284293
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the camera perspective bias in authentic videotaped interrogations: Implications for emerging reform in the criminal justice system

Abstract: Objective. Numerous previous experiments have established the existence of a camera perspective bias in evaluations of videotaped interrogations/confessions: videotapes that make the suspect more visually conspicuous than the interrogator(s) by virtue of focusing the camera on the suspect yield assessments of voluntariness and judgments of guilt that are greater than those found when alternative presentation formats are used. One limitation of this body of research is that all the interrogations/confessions us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
(37 reference statements)
0
27
0
1
Order By: Relevance
“…Specifically, when viewing videotapes of suspects' police interviews, the viewpoint the video takes (i.e. facing either the suspect or the police officer) influenced people's judgements about the degree to which a confession was given voluntarily, the likelihood that the suspect was guilty and the severity of the punishment s/he should receive (Lassiter and Irvine 1986;Lassiter et al 2001;) -even when it involved actual suspect interview footage (Lassiter et al 2009) in real life trial situations and even when the viewers were judges and police interrogators (Lassiter et al 2007). Later research revealed that this effect was largely a function of which person (the suspect or the police officer) the viewer had attended to the most -when allowed to view both equally (from the side), which of the two people the viewer looked at the longest was a complete mediator of the effect (Ware et al 2008).…”
Section: Why Is This Useful For Experimental Philosophy?mentioning
confidence: 99%
“…Specifically, when viewing videotapes of suspects' police interviews, the viewpoint the video takes (i.e. facing either the suspect or the police officer) influenced people's judgements about the degree to which a confession was given voluntarily, the likelihood that the suspect was guilty and the severity of the punishment s/he should receive (Lassiter and Irvine 1986;Lassiter et al 2001;) -even when it involved actual suspect interview footage (Lassiter et al 2009) in real life trial situations and even when the viewers were judges and police interrogators (Lassiter et al 2007). Later research revealed that this effect was largely a function of which person (the suspect or the police officer) the viewer had attended to the most -when allowed to view both equally (from the side), which of the two people the viewer looked at the longest was a complete mediator of the effect (Ware et al 2008).…”
Section: Why Is This Useful For Experimental Philosophy?mentioning
confidence: 99%
“…Şüphelilerin suçlu olup olmadığına ilişkin kararlar kameranın görüş açısının kime odaklandığına bağlı olarak değişebilmektedir. Örneğin, kameranın sorguyu yapanı da gösterdiği duruma kıyasla sadece şüpheliyi gösterdiği durumda karar vericiler soruşturma ortamının baskı/zorlama içermediğine, şüphelinin itirafı polis baskısı olmadan gönüllü bir şekilde verdiğine ve şüphelinin suçlu olduğuna daha çok inanma eğiliminde olmaktadır (Lassiter, Geers, Handley, Weiland ve Munhall, 2002;Lassiter, Geers, Munhall, Handley ve Beers, 2001;Lassiter ve Irvine, 1986;Lassiter, Ware, Ratcliff ve Irvin, 2009). Üstelik, bu etki yalnızca sıradan katılımcılar için değil polisler ve yargıçlar için de geçerli görünmektedir (Lassitter, Diamond, Schmidt ve Elek, 2007).…”
Section: Sorgunun Elektronik Kaydının Alınmasıunclassified
“…For example, individual differences in the motivation to think effortfully (Lassiter, Slaw, Briggs, & Scanlan, 1992) and in the capacity to reason specifically about complex causal relationships (Lassiter et al, 2005) do not moderate the camera perspective bias, nor is it reduced by situationally increasing observers' sense of accountability for their judgments (Lassiter, Munhall, Geers, Weiland, & Handley, 2001b). The bias has also been shown to occur across various types of crime (Lassiter et al, 1992), in the context of realistic trial simulations (Lassiter, Geers, Handley, Weiland, & Munhall, 2002b), with samples of college students and community members from disparate backgrounds (Lassiter et al, 2002b), and with authentic videotaped confessions recorded by police that depict actual suspects and interrogators (Lassiter, Ware, Ratcliff, & Irvin, 2009). Finally, relevant expertise does not mitigate the bias: both highly experienced trial judges and veteran police interrogators fall prey to it (Lassiter, Diamond, Schmidt, & Elek, 2007).…”
Section: The Camera Perspective Bias In Videotaped Interrogations-conmentioning
confidence: 99%